A novel coronene//Na2Ti3O7 dual-ion battery. (October 2017) - Dong, Shengyang; Li, Zhifei; Rodríguez-Pérez, Ismael A.; Jiang, Heng; Lu, Jun; Zhang, Xiaogang; Ji, Xiulei
Abstract: Here we construct a novel sodium dual-ion battery (Na-DIB) with a conventional alkyl/alkylene carbonate electrolyte by using reduced-graphene-oxide-coated Na2 Ti3 O7 (NTO@G) as the anode and coronene, a polycyclic aromatic hydrocarbon (PAH), as the cathode. The coronene//NTO@G configuration delivers a specific energy of 77 W h kg −1, based on the total active mass in both electrodes, and excellent cycling stability with 80% capacity retention after 5000 cycles. In addition, this device can work well in a wide range of temperatures from −20 to 40 °C. The results demonstrate a proof-of-concept Na-DIB that avoids the challenges of conventional dual-graphite DIBs by utilizing non-graphite intercalation anode and cathode, and a carbonate-based electrolyte without any additives. Graphical abstract: We report a new sodium dual ion battery (Na-DIB) with conventional alkyl carbonate electrolyte by using graphene coated Na2 Ti3 O7 as the anode and coronene, a polycyclic aromatic hydrocarbon, as the cathode. Benefiting from the novel nano-structural features and intercalation mechanisms, the Na-DIB demonstrates high energy density and long cycling life. Highlights: A new dual-ion battery configuration with NTO@G anode and polycyclic aromatic hydrocarbon (PAH) cathode. Moderate operating voltage at conventional alkyl carbonate electrolyte. The record-long cycling life of dual-ion batteries. Good electrochemical performance at different temperatures from −20 to 40 °C.